Charles Dickens : [a life defined by writing] - Slater, Michael (New Haven : Yale University Press, 2009)
This long-awaited biography, twenty years after the last major account, uncovers Dickens the man through the profession in which he excelled. Drawing on a lifetime's study of this prodigiously brilliant figure, Michael Slater explores the personal and emotional life, the high-profile public activities, the relentless travel, the charitable works, the amateur theatricals and the astonishing productivity. But the core focus is Dickens' career as a writer and professional author, covering not only his big novels but also his phenomenal output of other writing--letters, journalism, shorter fiction, plays, verses, essays, writings for children, travel books, speeches, and scripts for his public readings, and the relationships among them. Slater's account, rooted in deep research but written with affection, clarity, and economy, illuminates the context of each of the great novels while locating the life of the author within the imagination that created them. It highlights Dickens' boundless energy, his passion for order and fascination with disorder, his organizational genius, his deep concern for the poor and outrage at indifference towards them, his susceptibility towards young women, his love of Christmas and fairy tales, and his hatred of tyranny.
1. Early years : from Portsmouth to Chatham, 1812-1822 -- 2. Early years : London, 1822-1827 -- 3.'The Copperfield days', 1828-1835 -- 4. Break-through year, 1836 -- 5. Editing Bentley's Magazine, 1836-1837 -- 6. Periodicals into novels, 1837-1839 -- 7. The Master Humphrey experiment, 1840-1841 -- 8. America brought to book, 1842 -- 9.'The turning-point of his career' : England, Italy, England, 1842-1845 -- 10. An interlude :'daily nooses' and the noose itself, 1846 -- 11. Dombey and other dealings, 1846-1848 -- 12. From Dombey to Copperfield, 1848-1849 -- 13. Interweaving and conducting : writing David Copperfield and beginning Household words, 1849-1850 -- 14. The year of the guild, 1850-1851 -- 15. Writing Bleak house, 1852-1853 -- 16. Writing'For these times', 1853-1854 -- 17. Writing Little Dorrit-among other things, 1855-1857 -- 18. Drama and denouement : performing The Frozen deep and finishing Little Dorrit, 1857 -- 19. Writing off a marriage, 1857-1858 -- 20. Stories into scripts : the public readings, 1858 -- 21. Serials, series and stories : writing for All the year round, 1859-1861 -- 22. Christmas numbers, public readings, and'uncommercial' travels, 1861-1863 -- 23. Back to the'big brushes' : writing Our mutual friend, 1864-1865 -- 24. Last Christmas numbers, 1865-1867 -- 25. Writing, and reading, for America, 1867-1868 -- 26. Disappearances and deaths, 1868-1870 -- 27. Charles Dickens's explanations.
Includes bibliographical references (p. [624]-626) and index.
Keywords: Dickens, Charles, -- 1812-1870.; Authors, English -- 19th century -- Biography